RCN and Caracol news official journalistic profiles digitized content analysis through Facebook (2019)
Journalist’s task has been transformed throughouthistory, and especially, thanks to new technologiesadvancement. According to a survey conductedin 2012 by the Ministry of Information andCommunications Technology of Colombia, “80 %of respondents use the Internet. Besides, the largestincrease in network use has occurred in 1 and 2 strata,with a 17% of growth compared to the use they hadgiven to it in 2012. The survey also indicated that 54% of Colombians use the Internet daily, browsing anaverage of 2.6 hours” (MinTic 2012).Today, journalists not only seek and write news, butalso, implement strategies to improve news distributionand increase its traffic through web portals. Thisis a reason why the current article, describes thenews treatment given to digital information contentpublished by Caracol and RCN news in their officialprofiles, and through the digital social networkFacebook. Therefore, news portals evidenced themes,each news’ implemented digital production policy,and the digital content multimedia and hypertextualproduction structure distributed through a reticularexchange platform, are analyzed.